2008
DOI: 10.1099/jmm.0.47726-0
|View full text |Cite
|
Sign up to set email alerts
|

emm type diversity of β-haemolytic streptococci recovered in Chennai, India

Abstract: JMM Correspondence emm type diversity of b-haemolytic streptococci recovered in Chennai, India

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…The prevalence of emm types stG485.0 and stG166b was even higher in the invasive group (23.2 % and 16.2 %, respectively). These results are in accordance with other studies: emm types stG485.0 and stG6.1 were reported as being the most common types identified among patients with group G bacteremia in a hospital setting in Jerusalem [6], in Chennai, south India [16] and in a hospital setting in Northern Taiwan [17]. The total high prevalence of those emm types in all other isolates (noninvasive and carriage) indicates the likelihood of a possible reservoir for severe infections.…”
Section: Discussionsupporting
confidence: 93%
“…The prevalence of emm types stG485.0 and stG166b was even higher in the invasive group (23.2 % and 16.2 %, respectively). These results are in accordance with other studies: emm types stG485.0 and stG6.1 were reported as being the most common types identified among patients with group G bacteremia in a hospital setting in Jerusalem [6], in Chennai, south India [16] and in a hospital setting in Northern Taiwan [17]. The total high prevalence of those emm types in all other isolates (noninvasive and carriage) indicates the likelihood of a possible reservoir for severe infections.…”
Section: Discussionsupporting
confidence: 93%
“…17,18 In addition, although M proteins are present in non-GBS BHS [Group C Streptococcus (GCS)/Group G Streptococcus (GGS)], they are diverse, rendering a broadly protective M-based approach challenging. [19][20][21] Therefore, other approaches for development of a broadly protective vaccine have been considered. 22 One of a number of promising vaccine candidates is the recombinant streptococcal C5a peptidase (SCP) antigen, 23 which is conserved across BHS, and has shown preclinical efficacy against GAS and GBS.…”
mentioning
confidence: 99%
“…Reported literature on emm distribution among Indian GAS isolates is relatively limited (Dey et al 2005;Sagar et al 2004;Sindhulina et al 2008;Menon et al 2001Menon et al , 2008; however, a comparison of these studies shows that distinct differences do exist among the types identified among GAS isolated from Bangalore, Chennai and Chandigarh. Interestingly, types 12, 49, 71, 74 and to some extent type 1 are common to the above regions.…”
Section: Resultsmentioning
confidence: 97%